How Do Nutritional Warnings Work on Commercial Products? Results From a Hypothetical Choice Experiment - de Alcantara, Marcela; Ares, Gastón; Deliza, Rosires (Frontiers in Nutrition, 2022)
A large body of evidence assessing the effectiveness of front-of-package (FOP) nutrition labeling exists. Most experimental studies have been conducted with fictitious products. However, consumers’ perception depends on several products extrinsic factors such as brand. Understanding how strong brand associations influence the effectiveness of FOP nutrition labeling schemes may be crucial to informing policymaking. In this context, the aim of this work was to evaluate the effect of five different variants of nutritional warnings labels (black magnifier, red magnifier, black octagon, black triangle, and red circle) on consumers’ choice of commercial products, compared with two FOP nutrition labeling schemes: the guidelines daily amounts (GDAs) system and the traffic light system (TLS). An online randomized controlled trial with 1,932 participants was used to evaluate the effect of FOP nutrition labeling on participants’ choices in eight sets of three commercial products, available in the Brazilian marketplace. A multinomial logistic regression model was used to evaluate the influence of FOP nutrition labeling on participants’ likelihood of selecting the different products in the choice task. Results showed that nutritional warnings and the TLS significantly increased the likelihood of selecting none of the products instead of the least healthful product, or a healthier product, in at least one of the product categories compared with the GDA. Warnings tended to have a larger effect, suggesting their potential to encourage healthier food choices.